Two-year vessel healing after everolimus-eluting stent implantation: Serial assessment by optical coherence tomography. Issue 4 (April 2015) - Taniguchi, Yu; Otake, Hiromasa; Shinke, Toshiro; Nakagawa, Masayuki; Hariki, Hirotoshi; Inoue, Takumi; Osue, Tsuyoshi; Hiranuma, Noritoshi; Nishio, Ryo; Kinutani, Hiroto; Iwasaki, Masamichi; Konishi, Akihide; et al.
Abstract Background Previous reports have suggested the importance of delayed arterial healing and the development of neoatherosclerosis as major contributors to stent thrombosis and delayed restenosis. The difference of in vivo assessment of long-term vessel healing between first-generation drug-eluting stents and current generation everolimus-eluting stents (EESs) is limited. The aim of this study was to evaluate long-term arterial healing in EES in comparison with the first generation sirolimus-eluting stents (SES). Methods We evaluated 31 EES (23 patients) and 8 SES (7 patients) by serial optical coherence tomography at 12 months (mid-phase) and 24 months (late-phase) after stenting and evaluated the change in neointimal thickness (NIT), the percentages of uncovered struts, peri-strut low intensity area (PLIA; region around stent struts homogenously lower-intensity appearance than surrounding tissue), and thrombus. Results Although the average NIT showed no significant changes from the mid- to the late-phase follow-up in both EES and SES groups, the change in NIT and minimum lumen area was significantly larger in SES than EES (5.2 ± 29.4 vs. 37.2 ± 48.9; p = 0.02, −0.06 ± 0.36 vs. −0.45 ± 0.74; p = 0.04, respectively). The incidence of uncovered struts and struts with PLIA of EES was lower than those of SES, at both phases. Stents with in-stent thrombus of EES tended to be lower than that of SES at both phase follow-ups. Conclusion Although both SES and EES showed progressive luminal narrowing from the mid- to the late-phase follow-up, the extent of delayed lumen narrowing and delayed neointimal proliferation was significantly less in the second generation EES than the first generation SES. EESs seem to offer sustained stability in efficacy, without sacrificing safety, up to 2 years after implantation.